From national to regional narratives - Babić, Darko muzeolog (Array, 2012)
From their very formation nation states and national public museums have had a relationship characterized by mutual influence and interconnectedness. National museums played a prominent role by collected material culture with which they constructed grand narratives – significant for promoting the idea of nation. The overarching notion of national identity pushed the local and regional identities to the margins. In the early 1990s Europe was a place of political changes especially evident in the states of the former Eastern Block where the fall of socialism (communism) gave rise to new nationalist feelings. In certain cases, as in Yugoslavia, national feelings led to war, and consequently six new nation states were born over a decade, one of which was Croatia. The first, and the only, Croatian National Museum was formed in 1846 assuming a similar role of other national museum throughout Europe. It ceased to exist in 1939. From 1991, when Croatia was recognized as an independent country, the need for a national museum has resurfaced again. Regardless of numerous suggested ideas and proposals for the establishment of a national museum – ranging from 19th century models to a more contemporary museological notion of a museum’s role in society – Croatia still does not have a national museum. So, the question is whether and how should a relatively newly established country enhance its identity through a national museum and what sort of museum should that be. Unlike the conventional museum practices of collecting, research and communicating of segmented cultural reality in isolating conditions (building), the authors of the paper propose the concept of a national museum which derives from the theoretical and practical standpoint of ecomuseology, that is, the concept of a national eco-museum, in its physical and virtual form. Taking into account a great cultural and geographical diversity of Croatia, which is its important characteristic, this museum could represent Croatians if organized according to a model which fosters regional characteristics – one that stays within the state boundaries but that is conceptually decentralized. Empowerment of regionalism could furthermore enable cross-border cooperation between communities which are much more similar culturally and geographically than individual cultural entities within Croatia or any other nation state. Such a development projected in the future might lead to the formation throughout Europe of numerous museums of regions which could more genuinely create sense of place through regional narratives, and thereby replace the domination the national museums have had for such a long time.